Improving Students' Creative Thinking Abilitiesthrough Problem Based Learning Model - Saniria Benu; Harun Y. Natonis (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the application of problem-based learning models (PBL) in improving students' creative thinking skills. Creative thinking skills are one of the 21st century skills that are very much needed in facing future challenges. Problem-based learning models are seen as an effective approach to developing creative thinking skills because they provide students with the opportunity to explore innovative solutions to contextual problems. The research method used is a literature study by analyzing various relevant literature sources from 2019-2024. The results of the analysis show that the application of problem-based learning models can improve students' creative thinking skills through the stages of problem orientation, organizing students to learn, guiding individual and group investigations, developing and presenting work results, and analyzing and evaluating the problem-solving process. The conclusion of this study shows that problem-based learning models have proven effective in improving students' creative thinking skills with indicators of fluency, flexibility, originality, and elaboration.